Resilience of Micro, Small, and Medium Enterprises Based on Islamic Entrepreneurship - Kasim, Sinta; Hamzah, Muh. Nasir; Kadir, Amiruddin; Muhammad Wahyuddin Abdullah (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have a very important role in socio-economic development in Indonesia. But the problem that often occurs is its vulnerability to changes that result in losses. This is because MSMEs have limited resources. In fact, MSMEs have proven to be a safety valve for the national economy and are able to survive and become economic drivers, especially during times of economic crisis.  The results showed that the resilience of MSMEs in terms of their competitive advantage is easily replicated and replaced at any time, depending on their ability to manage and run a business. So it takes resources and capabilities to achieve core compatibility. The resilience of MSMEs in facing uncertain crisis conditions must be supported by the application of Islamic Entrepreneurship, this is because resilience is influenced by two factors, namely Internal and External. These internal factors cannot be eliminated by humans in running life, namely spirituality, faith, and optimism. Because sharia refers to the command of Allah Swt.